5-Abstracts Communications Orales -Neuroradiologie et Imagerie ORL_ JRANF 2024_JAIM 2024_16.3 - OP. LAWANI; NEOSSI GUENA Mathurin; MOIFO Boniface; GUIABA KEKKE Judith; NIANG Ibrahima; S GUIDAH; NIANG Fallou Galass; K.E. TANOH; KOUANDONGUI BANGUE SONGROU Francky; Stéphane Aimé KOUZOU; et al. (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2024)
5-Abstracts Communications Orales -Neuroradiologie et Imagerie ORL_ JRANF 2024_JAIM 2024_16.3